Serum antibody response to polysaccharides in children with recurrent respiratory tract infections - López Yap, Alberto (2001)
We evaluated children (15-months old and older) with recurrent upper respiratory tract infections and normal levels of immunoglobulins in serum for specific polysaccharide immunodeficiency using an enzyme-linked immunosorbent assay method. Results showed that of 12 patients vaccinated with Act-HIB vaccine, one did not develop specific antibodies to Haemophilus influenzae type b, demonstrating that such immunodeficiency is present in Costa Rican children.